Imagery of negative interpersonal experiences influence the neural mechanisms of social interaction. (17th September 2021) - Brandi, Marie-Luise; Lahnakoski, Juha M.; Kopf-Beck, Johannes; Nolte, Tobias; Brückl, Tanja M.; Schilbach, Leonhard
Abstract: Negative interpersonal experiences are a key contributor to psychiatric disorders. While previous research has shown that negative interpersonal experiences influence social cognition, less is known about the effects on participation in social interactions and the underlying neurobiology. To address this, we developed a new naturalistic version of a gaze-contingent paradigm using real video sequences of gaze behaviour that respond to the participants' gaze in real-time in order to create a believable and continuous interactive social situation. Additionally, participants listened to two autobiographical audio-scripts that guided them to imagine a recent stressful and a relaxing situation and performed the gaze-based social interaction task before and after the presentation of either the stressful or the relaxing audio-script. Our results demonstrate that the social interaction task robustly recruits brain areas with known involvement in social cognition, namely the medial prefrontal cortex, bilateral temporoparietal junction, superior temporal sulcus as well as the precuneus. Imagery of negative interpersonal experiences compared to relaxing imagery led to a prolonged change in affective state and to increased brain responses during the subsequent social interaction paradigm in the temporoparietal junction, medial prefrontal cortex, anterior cingulate cortex, precuneus and inferior frontal gyrus. Taken together this study presents a new naturalistic social interaction paradigm suitable to study the neural mechanisms of social interaction and the results demonstrate that the imagery of negative interpersonal experiences affects social interaction on neural levels. Highlights: The naturalistic simulation of a gaze-based social interaction recruits core regions of the mentalizing network. Imagery of negative interpersonal experiences influences negative affect. Imagery of negative interpersonal experiences increases brain responses of parts of the mentalizing network and brain areas related to stress processing.